PERAN PENDIDIKAN KEAKSARAAN FUNGSIONAL BAGI MASYARAKAT BUTA AKSARA - Naila Binta Azizah; Arin Khairunnisa (Nusantara Hasana Journal, 2023)
Literacy education is a form of non-formal education services for illiterate citizens to learn to read, write, and count. Literacy Education consists of Basic Literacy Education and Advanced Literacy Education. Literacy Education is an educational service for Latin illiterate citizens so that they have the ability to read, write, count, speak Indonesian, and analyze so as to provide opportunities for self-actualization of potential. (Permendikbud RI No. 45 of 2015 Chapter 1 Article 1). The formulation of the problem to be discussed is that many people in Indonesia are illiterate. Illiteracy can be referred to as the inability of a person to use language and use it to understand a text, listen to words, express or express it in written and spoken form. The method used is the method of literature study. Collecting data cited from various sources such as articles. Or it can also be called the Traditional Review method, which means literature review. This method depends on the knowledge and experience of the researcher. The results of the review can be concluded that in non-formal education, it always provides various access needs for the community with various programs, one of which is literacy education which is very useful for reducing illiteracy in both early and old age.